4-Year Outcomes After Left Atrial Appendage Closure Versus Nonwarfarin Oral Anticoagulation for Atrial Fibrillation - Osmancik, Pavel; Herman, Dalibor; Neuzil, Petr; Hala, Pavel; Taborsky, Milos; Kala, Petr; Poloczek, Martin; Stasek, Josef; Haman, Ludek; Branny, Marian; Chovancik, Jan; Cervinka, Pavel; et al. (Journal of the American College of Cardiology, 2022)
BACKGROUND: The PRAGUE-17 (Left Atrial Appendage Closure vs Novel Anticoagulation Agents in Atrial Fibrillation) trial demonstrated that left atrial appendage closure (LAAC) was noninferior to nonwarfarin direct oral anticoagulants (DOACs) for preventing major neurological, cardiovascular, or bleeding events in patients with atrial fibrillation (AF) who were at high risk. OBJECTIVES: This study sought to assess the prespecified long-term (4-year) outcomes in PRAGUE-17. METHODS: PRAGUE-17 was a randomized noninferiority trial comparing percutaneous LAAC (Watchman or Amulet) with DOACs (95% apixaban) in patients with nonvalvular AF and with a history of cardioembolism, clinically-relevant bleeding, or both CHA2DS2-VASc ≥3 and HASBLED ≥2. The primary endpoint was a composite of cardioembolic events (stroke, transient ischemic attack, or systemic embolism), cardiovascular death, clinically relevant bleeding, or procedure-/device-related complications (LAAC group only). The primary analysis was modified intention-to-treat. RESULTS: This study randomized 402 patients with AF (201 per group, age 73.3 ± 7.0 years, 65.7% male, CHA2DS2-VASc 4.7 ±1.5, HASBLED 3.1 ± 0.9). After 3.5 years median follow-up (1,354 patient-years), LAAC was noninferior to DOACs for the primary endpoint by modified intention-to-treat (subdistribution HR [sHR]: 0.81; 95% CI: 0.56-1.18; P = 0.27; P for noninferiority = 0.006). For the components of the composite endpoint, the corresponding sHRs were 0.68 (95% CI: 0.39-1.20; P = 0.19) for cardiovascular death, 1.14 (95% CI: 0.56-2.30; P = 0.72) for all-stroke/transient ischemic attack, 0.75 (95% CI: 0.44-1.27; P = 0.28) for clinically relevant bleeding, and 0.55 (95% CI: 0.31-0.97; P = 0.039) for nonprocedural clinically relevant bleeding. The primary endpoint outcomes were similar in the per-protocol (sHR: 0.80; 95% CI: 0.54-1.18; P = 0.25) and on-treatment (sHR: 0.82; 95% CI: 0.56-1.20; P = 0.30) analyses. CONCLUSIONS: In long-term follow-up of PRAGUE-17, LAAC remains noninferior to DOACs for preventing major cardiovascular, neurological, or bleeding events. Furthermore, nonprocedural bleeding was significantly reduced with LAAC. (PRAGUE-17 [Left Atrial Appendage Closure vs Novel Anticoagulation Agents in Atrial Fibrillation]; NCT02426944).
Keywords: mužské pohlaví; Male; senioři; cévní mozková příhoda; Hemorrhage; Female; Humans; Ischemic Attack, Transient; left atrial appendage closure; atrial fibrillation; tranzitorní ischemická ataka; následné studie; lidé; Follow-Up Studies; Prospective Studies; ženské pohlaví; Atrial Appendage; fibrilace síní; inhibitory faktoru Xa; dire oral anticoagulant; oral anticoagulation; krvácení; Stroke; Factor Xa Inhibitors; prospektivní studie; síňové ouško; Atrial Fibrillation; Aged; cardioembolism